Exploring The Psychological Impact, Decision-Making Process, Resilience, Emotional Recovery, and Forgiveness in Wives Affected by Husband’s Infidelity - Abdul Haris Fitri Anto; Adlin Malikah Hanun; Fitria Tahta Alfina; Muhammad Farid Novian; Poetri Lailatuz Zuhroh (International Conference on Sustainable Health Promotion, 2025)
A husband’s infidelity can precipitate significant psychological repercussions for the wife. These repercussions often manifest as anger, sadness, disappointment, feelings of worthlessness, betrayal, and hatred. Additionally, wives subjected to their husband’s infidelity may exhibit symptoms of depression, stress, and anxiety disorders. Despite extensive research on the psychological dynamics of wives affected by infidelity, findings have been varied. Therefore, this article aims to synthesise and critically analyse existing research to provide a comprehensive understanding and inspire future studies. Employing a scoping review method, literature selection was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The data were drawn from the literature on Google Scholar, covering publications from the last decade (2014-2024). Furthermore, the inclusion criteria included: empirical research, full-text available, wives as the research participants, and the result/discussion sections focus on psychological dynamics as the victims of the husband’s infidelity. While literature research, books/e-books, book chapters, unaccessible full-texts, final assignment repositories, and working papers were excluded from the criteria. The screening resulted in the identification of 30 relevant articles. The analysis revealed several core themes: the psychological impact of infidelity, the decision-making processes of wives post-infidelity, resilience among wives experiencing infidelity, strategies for emotional recovery, and the role of forgiveness towards unfaithful husbands. These themes will be further explored in the discussion section.